2021
DOI: 10.1088/1367-2630/abf459
|View full text |Cite
|
Sign up to set email alerts
|

Community lockdowns in social networks hardly mitigate epidemic spreading

Abstract: Community lockdowns and travel restrictions are commonly employed to decelerate epidemic spreading. We here use a stochastic susceptible-infectious-recovered model on different social networks to determine when and to what degree such lockdowns are likely to be effective. Our research shows that community lockdowns are effective only if the links outside of the communities are virtually completely sealed off. The benefits of targeting specifically these links, as opposed to links uniformly at random across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…This network model produces interaction structures with genuine characteristics of social networks [58] , [59] , [60] . Networks embedded in hyperbolic spaces exhibit a small diameter, strong clustering, community structure, and a heterogeneous degree distribution and are therefore commonly used to simulate various social phenomena, including epidemics [61] , [62] , [63] . In our study, we utilized the geometric preferential attachment model, where each newly added node i is mapped into the hyperbolic disc with randomly assigned polar coordinates: …”
Section: Computational Modelmentioning
confidence: 99%
“…This network model produces interaction structures with genuine characteristics of social networks [58] , [59] , [60] . Networks embedded in hyperbolic spaces exhibit a small diameter, strong clustering, community structure, and a heterogeneous degree distribution and are therefore commonly used to simulate various social phenomena, including epidemics [61] , [62] , [63] . In our study, we utilized the geometric preferential attachment model, where each newly added node i is mapped into the hyperbolic disc with randomly assigned polar coordinates: …”
Section: Computational Modelmentioning
confidence: 99%
“…Chen et al [23], Gong et al [25], and Min et al [69] used the SIR model to simulate the epidemic dynamics in the generated network. To study the effectiveness of community blockade in preventing the spread of epidemics, Gosak et al [95] simulated a random SIR model on different social networks. e SIR model helps to study immune strategies.…”
Section: Related Workmentioning
confidence: 99%
“…Taking into account the development of appropriate vaccination strategies on the dynamic contact network, Shahzamal et al [131] proposed a strategy based on local contact information, called the individual's movement-based vaccination strategy. Numerical simulations by Yang [17] and Parousis-Orthodox [95] showed that networks with a higher modularity index are more likely to be affected by the central vaccination technology between nodes, so immunization of central nodes is a good way to alleviate epidemics. Based on the concept of independent set, Huang [74] proposed a new immune strategy for complex networks, an immune method with the largest vertex of independent concentration, called independent set target immunity.…”
Section: Vaccination Strategymentioning
confidence: 99%
“…This model indicates that disregarding social distancing and hygiene concepts can cause devastating effects on the human population. On the other hand, as shown in [20], lockdowns limited to communities together with travel restrictions are commonly employed to reduce epidemic spreading, but not totally effective if the people are not completely sealed off. In this contribution, a stochastic model on different social networks is considered to determine the level of effectiveness of lockdowns and to identify which social network compartments should be considered.…”
Section: Literature Reviewmentioning
confidence: 99%